ANALYSIS OF FACTORS INFLUENCING INDONESIA'S TOBACCO EXPORTS 1975-2018 - Charisa Febby Shelina; Hadi Sasana (Transpublika Publisher, 2022)
This study aims to examine the effect of Indonesia's real GDP, the area of Indonesian tobacco cultivation, and the quantity of Indonesian tobacco production on the quantity of Indonesian exports. This study uses Autoregressive Distributed Lag (ARDL) with time series data from 1975 to 2018 as its analytic tool. The information contained in this study was compiled from periodic reports published by organizations such as the Directorate General of Plantations and the World Bank between 1975 and 2018. The probability value for the number of exports should not exceed 5% if the test results for the short-term real GDP of Indonesia are positive and non-significant. Long-term, the amount of national tobacco production has a positive and significant effect on the quantity of tobacco exports from Indonesia. The long-term stability of the CUSUM and CUSUMQ test results for both analytical models